(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Despite the wide range of advantages of non-steroidal anti-inflammatory drugs (NSAIDs) such as diclofenac, their abuse can have a deleterious impact on the hepatorenal system. This study evaluated the histopathological and molecular effects of NSAIDs-induced hepatorenal toxicity on the expression of TGFβ and Nrf2 in the liver and kidneys of adult male Wistar rats treated with methanolic leaf extracts of Cymbopogon citratus (lemon grass). Twenty adult male Wistar rats were randomly divided into four groups. The first group were the unexposed control rats administered with distilled water only, while the test groups (II-IV) were orally administered with diclofenac at a standard dosage of 5mg/kg/BW. The rats in groups III and IV were administered with methanolic extract of Cymbopogon citratus at 100mg/kg/BW and 200mg/kg/BW respectively. After 28 days, the rats were euthanized by cervical dislocation, and the liver and kidneys were histologically processed. mRNA expression of nuclear factor erythroid 2-related factor 2 (Nrf-2) and transforming growth factor beta (TGF-β) was then analyzed. The results revealed significant pathological alterations in the histoarchitecture of the livers and kidneys of the untreated NSAIDs-exposed rats with the administration of Cymbopogon citratus effectively reducing oxidative damage by modulating the expression of Nrf-2 and TGF-β while also ameliorating the histological derangement observed in the studied organs. Cymbopogon citratus modulates the expression of TGF-β and Nrf-2 in the liver and kidneys of the experimental animals consequently mitigating diclofenac-induced oxidative damage in the studied organs.